Reconsidering Assumptions of Adolescent and Young Adult Severe Acute Respiratory Syndrome Coronavirus 2 Transmission Dynamics. (7th September 2020) - Guilamo-Ramos, Vincent; Benzekri, Adam; Thimm-Kaiser, Marco; Hidalgo, Andrew; Perlman, David C
Abstract: Evidence regarding the important role of adolescents and young adults (AYA) in accelerating and sustaining coronavirus disease 2019 (COVID-19) outbreaks is growing. Furthermore, data suggest that 2 known factors that contribute to high severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmissibility—presymptomatic transmission and asymptomatic case presentations—may be amplified in AYA. However, AYA have not been prioritized as a key population in the public health response to the COVID-19 pandemic. Policy decisions that limit public health attention to AYA and are driven by the assumption of insignificant forward transmission from AYA pose a risk of inadvertent reinvigoration of local transmission dynamics. In this viewpoint, we highlight evidence regarding the increased potential of AYA to transmit SARS-CoV-2 that, to date, has received little attention, discuss adolescent and young adult–specific considerations for future COVID-19 control measures, and provide applied programmatic suggestions.